Hybrid Elliptic Curve Cryptography for Secured Cloud Computing - Sakthivel, G; Madhubala, P (International Journal of Computer Sciences and Engineering, 2019)
This paper presents a secure cloud storage scheme based on hybrid cryptosystem, which consists of Elliptic Curve Cryptography (ECC), Advanced Encryption Standard (AES), and one-way hash function. Here, the data owner exports large volume of encrypted data to a cloud storage provider, the Electronic cryptography is a public key or asymmetric key means that the encryption key and decryption key are different. In many applications like military databases confidential video conferencing, medical imaging system, online personal photograph album security is very essential. Also, in industrial process wide usage of images can turn it into a resource and asset. So, it is important to protect confidential images data from unauthorized access. this paper proposes elliptical curve cryptography-based security mechanism and ant colony optimization based secured key management technique. The proposed system provides better space complexity than existing RSA and CRT, and the ACO improves optimality.